2021
DOI: 10.1101/2021.10.05.463240
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sequencing of Argonaute-bound miRNA/mRNA hybrids reveals regulation of the unfolded protein response by microRNA-320a

Abstract: MicroRNAs (miRNA) are short non-coding RNAs widely implicated in gene regulation. Most metazoan miRNAs utilize the RNase III enzymes Drosha and Dicer for biogenesis. One notable exception is the RNA polymerase II transcription start sites (TSS) miRNAs whose biogenesis does not require Drosha. The functional importance of the TSS-miRNA biogenesis is uncertain. To better understand the function of TSS-miRNAs, we applied a modified Crosslinking, Ligation, and Sequencing of Hybrids on Argonaute (AGO-qCLASH) to ide… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 98 publications
(170 reference statements)
1
1
0
Order By: Relevance
“…Fig 11). Previous studies reported a correlation between the number of detected hybrids and the expression levels of its miRNA and mRNA components [14,24]. These correlations hold true for our matching total and the small RNA-seq data when taking the total count across the replicates (Fig 4 .B, left panels).…”
Section: Contribution Of Mirnas To the Resistant Phenotypesupporting
confidence: 79%
See 1 more Smart Citation
“…Fig 11). Previous studies reported a correlation between the number of detected hybrids and the expression levels of its miRNA and mRNA components [14,24]. These correlations hold true for our matching total and the small RNA-seq data when taking the total count across the replicates (Fig 4 .B, left panels).…”
Section: Contribution Of Mirnas To the Resistant Phenotypesupporting
confidence: 79%
“…Fig 12). Previous studies reported a correlation between the number of detected hybrids and the expression levels of its miRNA and mRNA components [15,31].…”
Section: Contribution Of Mirnas To the Resistant Phenotypementioning
confidence: 95%